2020
DOI: 10.3390/ncrna6020015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Expression of Long Non-Coding RNAs Throughout Parasite Sexual and Neural Maturation in Schistosoma Japonicum

Abstract: Schistosoma japonicum is a flatworm that causes schistosomiasis, a neglected tropical disease. S. japonicum RNA-Seq analyses has been previously reported in the literature on females and males obtained during sexual maturation from 14 to 28 days post-infection in mouse, resulting in the identification of protein-coding genes and pathways, whose expression levels were related to sexual development. However, this work did not include an analysis of long non-coding RNAs (lncRNAs). Here, we applied a pipeline to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
(84 reference statements)
2
15
0
Order By: Relevance
“…In this study, we experimentally validated 25 Sm-lncRNAs from a 47 Sm-lncRNA set that were previously predicted by in silico analysis [12]. Of this validated lncRNA set, almost all molecules showed a stagespeci c expression level, demonstrating the potential regulatory role played by lncRNAs and corroborating the few other studies found in the literature [9,12,14,22,23]. The developmental stages analyzed here need to face a freshwater-mammalian body and even Th1-Th2 immune transition pressures [24], which can explain the variability in the expression of regulatory molecules at each developmental stage [25].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, we experimentally validated 25 Sm-lncRNAs from a 47 Sm-lncRNA set that were previously predicted by in silico analysis [12]. Of this validated lncRNA set, almost all molecules showed a stagespeci c expression level, demonstrating the potential regulatory role played by lncRNAs and corroborating the few other studies found in the literature [9,12,14,22,23]. The developmental stages analyzed here need to face a freshwater-mammalian body and even Th1-Th2 immune transition pressures [24], which can explain the variability in the expression of regulatory molecules at each developmental stage [25].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, location characterization can allow predictions about lncRNA functions in cis, based on their putative target genes [7,8]. Recently, Schistosoma lncRNAs have also been investigated for their potential functions [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While some of them surely represent assembly artifacts, others might be functionally relevant. According to the recent publications [66][67][68][69][70][71] long non-coding RNAs (ncRNAs) are one of the important regulators of gene expression and indispensable components of genetic networks. Analysis of the diversity and roles of non-coding RNAs in the Psilostomatidae is, therefore, a promising research direction for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of specific lncR-NAs in hepatic diseases has been described, and hepatic stellate cells trans-differentiation is regulated by different lncRNAs [19][20][21] A previous study employed different tools to study differential gene expression patterns occurring in response to Schistosoma infections [22]. Recently, Schistosoma lncRNAs have also been investigated for their potential functions [23][24][25][26][27][28][29]. However, lncRNAs in Schistosoma japonicum-infected mouse liver and spleen samples have not been investigated by RNA-Seq.…”
Section: Introductionmentioning
confidence: 99%